Computers, privacy and data protection an element of choice - Gutwirth, Serge; Poullet, Yves; De Hert, Paul; Leenes, Ronald; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Privacy and data protection have never been static. On the contrary, the history of the last 40 years shows the reverse. New issues and challenges continue to emerge, requiring an ongoing process of interpreting their effect in terms of reach, objectives and their deeper significance. Indeed, the consequences of technological applications due to unprecedented storage, processing and transmission capacities and to the possibilities of miniaturization, convergence, interoperability and ubiquity, represent powerful triggers and challenges to emerging developments, but they are certainly not the only determining factor. The current developments are also linked to many other sources of action and change, such as business models, security policies, population management, police work and law enforcement, leisure, culture, health policies, practices in the real and in the virtual world and so on. In the face of such dynamism, the "element of choice unambiguously evokes both the need to collectively take responsibility and direct those developments in a desirable direction, providing the ambit to influence and steer the course of things in a way that matches our expectations not only toward privacy and data protection, but also more broadly, to the kind of world we are building. This challenge is not an easy one since all big policy choices we might be willing to make are conditioned by a myriad of small decisions and bifurcations that have already set many small switches in irreversible positions. In one way or another, all the contributions to this book express the complexity of making choices regarding issues of privacy and data protection. This is all the more relevant given that the 1995 EC Data Protection Directive, the centerpiece of European data protection, is being revised as these sentences are written
Introduction.- Part 1 Building and Rebuilding Legal Concepts for Privacy and Data Protection.- Chapter 1 The German Constitutional Court Judgment on Data Retention: Proportionality Overrides Unlimited Surveillance (Doesn?t It?); Katja de Vries, Rocco Bellanova, Paul De Hert and Serge Gutwirth.- Chapter 2 The Noise in the Archive: Oblivion in the Age of Total Recall; Jean-François Blanchette.- Chapter 3 Property in personal data. Second life of an old idea in the age of cloud computing, chain informatisation, and ambient intelligence; Nadezhda Purtova.- Chapter 4, Right to Personal Identity. The Challenges of Ambient Intelligence and the Need for a New Legal Conceptualization ; Norberto Nuno Gomes de Andrade.- Part 2 The Dark Side: Suspicions, Distrust and Surveillance.- Chapter 5 Frames from the life and death of Jean Charles de Menezes; Amos Bianchi & Denis J. Roio (a.k.a. Jaromil).- Chapter 6 Regulating Privacy: Vocabularies of Motive in Legislating Right of Access to Criminal Records in Sweden; Christel Backman.- Chapter 7 Ubiquitous computing, privacy and data protection: options and limitations to reconcile the unprecedented contradictions; Johann Čas.- Chapter 8 Franziska Boehm, EU PNR: European Flight passengers under general suspicion. The envisaged European model of analyzing flight passenger data.- Chapter 9 Options for securing PCs against phishing and espionage. A report from the EU-project "Open Trusted Computing"; Arnd Weber and Dirk Weber.- Part 3 Privacy Practices as Vectors of Reflection.- Chapter 10 Keeping up appearances: Audience segregation in social network sites; Bibi Van den Berg and Ronald Leenes.- Chapter 11 Avatars out of Control. Gazira Babeli, Pose Balls and ?Rape? in Second Life; Katja De Vries.- Chapter 12 Privacy as a practice: exploring the relational and spatial dynamics of HIV-related information seeking; Fadhila Mazanderani and Ian Brown.- Chapter 13 Rise and Phall: Lessons from the Phorm Saga; Paul Bernal.- Chapter 14 Disclosing or protecting? Teenagers online self-disclosure; Michel Walrave and Wannes Heirman.- Chapter 15 Why Adopting Privacy Enhancing Technologies (PETs) Takes So Much Time; John J. Borking.- Part 4 Privacy and Data Protection in the Cloud.- Chapter 16 Can a Cloud be Really Secure? A Socratic Dialogue; Gurpreet Dhillon and Ella Kolkowska.- Chapter 17 Privacy Regulations for Cloud Computing. Compliance and Implementation in Theory and Practice; Joep Ruiter and Martijn Warnier.- Chapter 18 Data Protection in the Clouds ; Yves Poullet, Jean-Marc Van Gyseghem, Jean-Philippe Moiny, Jacques Gérard and Claire Gayrel.- Chapter 19 Privacy-preserving Mining of Association Rules from Outsourced Transaction Databases; Fosca Giannotti, Laks V.S. Lakshmanan, Anna Monreale, Dino Pedreschi and Hui (Wendy) Wang.- Chapter 20 Access Control in Cloud-on-GRID Systems: the PerfCloud Case Study; Valentina Casola, Raffaele Lettiero, Massimiliano Rak and Umberto Villano.- Chapter 21 Security and privacy in the clouds: a bird?s eye view; Wolter Pieters
Includes bibliographical references
Electronic reproduction.
Keywords: Computer security; Data protection; Computers -- Access control